Productive Waqf and Innovation of Sharia Social Instruments: Strategies for Strengthening the Ummah's Economy - Pane, Sanusi Gazali (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the role of productive waqf and the innovation of Islamic social finance instruments as strategic tools for strengthening the economic empowerment of the Muslim community. Productive waqf is increasingly recognized as a long-term mechanism capable of generating sustainable socio-economic benefits through the professional and transparent management of waqf assets. However, its implementation still faces several challenges, including limited public literacy on waqf, inadequate institutional capacity of nazhir, and the suboptimal development of innovative Islamic social finance instruments that support productive waqf initiatives. Using a descriptive qualitative approach, this research examines relevant literature, regulatory frameworks, and empirical findings related to waqf management and Islamic social finance. The results indicate that digital innovations such as waqf-based crowdfunding, technology-enabled cash waqf, and the integration of Islamic finance with productive sectors have significant potential to enhance the effectiveness and impact of productive waqf. The study emphasizes the importance of collaboration among government bodies, waqf institutions, Islamic financial institutions, and the wider community to build a more professional, accountable, and impactful productive waqf ecosystem. These findings are expected to contribute to policy development, nazhir capacity building, and future innovation models in Islamic social finance.